Studies on deacetoxy/deacetylcephalosporin C synthase - Pereira, I; Pereira, Inês Antunes Cardoso (1993)
﻿ This thesis describes an investigation of the mechanism of the bifunctional, a-ketoglutarate dependent dioxygenase, deacetoxy/deacetylcephalosporin C synthase (DAOC/DACS), which catalyses the ring-expansion of penicillin N to deacetoxycephalosporin C (DAOC) and the hydroxylation of this to deacetylcephalosporin C (DAC). The conversion of the unnatural substrate 3-exomethylene cephalosporin C by DAOC/DACS has been investigated in detail. A new metabolite was isolated from incubations of the deuterated [4-2H]-3-exomethylene cephalosporin C, and was identified as the 3β-spiroepoxide cepham, (2Ṟ,3Ṟ,6Ṟ,7Ṟ)-l-aza-[2-2H]-3-spiroepoxy-7-[(5Ṟ)-5-amino- 5-carboxypentanamido]-8-oxo-5-thiabicyclo[4.2.0]octane-2-carboxylic acid. The results obtained indicate that this metabolite is a shunt product whose formation is enhanced by the operation of a deuterium kinetic isotope effect on an enzyme-bound intermediate. It has also been found that this 3β-spiroepoxide cepham is further converted by DAOC/DACS to 3-formyl cephalosporoate products. The mechanism of oxygenation of DAOC/DACS was investigated through 18O-labelling studies. Incubations of [2-13C,3-2H]penicillin N and [4-2H]-3-exomethylene cephalosporin C with DAOC/DACS were carried out under 18O2 or in H218O. Incorporation of 18O-label into the products [3-13C]DAC, [3-13C,4-²H]-3β-hydroxycepham and 3β-spiroepoxide cepham was observed from both sources. The results suggest that intermediates capable of oxygen-exchange are formed during the enzymatic reactions. Two substrate analogues, the 5-epipenicillin N and the 2β-difluoromethyl penicillin N, have been synthesised in order to probe the substrate specificity of DAOC/DACS with respect to the ring-expansion activity. The 5-epipenicillin N was not accepted as a substrate by DAOC/DACS, and the observations made indicate that it was unstable under the incubation conditions. No product was either observed from incubations of the 2β-difluoromethyl penicillin N with DAOC/DACS, although bioassay tests suggested a cephem product had been formed in very small amounts. Finally, the results of a substrate specificity comparison between the soluble recombinant enzymes deacetoxy/deacetylcephalosporin C synthase (DAOC/DACS) from Cephalosporium acremonium and deacetoxycephalosporin C synthase (DAOCS) from Streptomyces clavuligerus are described.